Nuisance control in renovation works of public hospital / Alyaa Anisah Azmi - Alyaa Anisah, Azmi (2018)
A hospital that is undergoing renovation should have specific cautions because it will create disturbance to the user as the renovation works can cause excessive nuisance. Control measures to reduce the nuisance during hospital renovation are thus necessary. Hence, the research is to understand how the method to reduce nuisance used can improve the level of satisfaction of the public users. In order to achieve the aim, questionnaire were distributed to the users of the building and the contractor in charge in a public hospital. The data were analysed using Statistical Package for Social Science (SPSS). From the data, the most critical types of nuisance that occured in the buildings are renovation works cause traffic disturbance to people. The highest rank of agreement responded by the users towards the method used by the contractor was the contractor provides tight and enough partition. Lastly, most of the respondents satisfied with the method used by the contractor. Thus, it is suggested that there are area of improvement that still can be improved by the contractor to reduce nuisance in the future.